THE RELATIONSHIP OF HOSPITAL WEBSITE INFORMATION QUALITY AND PATIENT SATISFACTION IN EAST JAVA - Caren Theresia; Irwan Syahrir (Global Journal of Health Administration, 2025)
Objective: the impact of online services and administrative information on patient satisfaction in Type C and D hospitals in East Java Province, using Google Review ratings as a measure of satisfaction. Methods: This quantitative study employs a descriptive-analytic design with a cross-sectional approach. The sample consists of Type C and D hospitals in East Java that have official websites and at least 20 Google Review ratings. Data were collected through content observation of hospital websites and extraction of ratings and comments from Google Reviews. Results: The findings indicate that Google Review ratings do not significantly influence the appearance or content of hospital websites. The success of digital services is more affected by organizational factors, technological aspects, and internal policies that support the implementation and development of information technology. Website design quality and user experience are critical factors in the development of hospital digital services. Conclusion: The study recommends that hospitals enhance website design quality and digital services with strong support from internal policies. Evaluating the effectiveness of digital services should involve more objective and comprehensive indicators to better improve patient satisfaction in the current digital era.